Mathematics for reliability engineering : modern concepts and applications - Ram, Mangey; Xing, Liudong; Appiah, Emmanuel A.; Bai, Guoqing; Chen, Liwei; Chen, Ying; Chen, Yuan; Chi, Yuanying; Coit, David W.; Dui, Hongyan; Gao, Kaiye; Ghaleb, Fares Ahmad; et al. (De Gruyter, 2021)
"Reliability is a fundamental criterium in engineering systems. This book shows innovative concepts and applications of mathematics in solving reliability problems. The contents address in particular the interaction between engineers and mathematicians, as well as the cross-fertilization of science and technology. It bridges the gap between theory and practice to aid in practical problem-solving in various contexts."--Publisher
Keywords: Reliability (Engineering); Systems engineering.; Engineering mathematics.; elektronické knihy; electronic books